Two new species of Halicyclops (Copepoda, Cyclopoida) from the estuarine interstitial waters in South Korea - Chang, Cheon Young; Lee, Jimin (Zootaxa, 2012)
Two new cyclopoid species belonging to the genus Halicyclops Norman, 1903 are described from brackish waters in South Korea: H. lanceolatus sp. nov. and H. pumilus sp. nov. Halicyclops lanceolatus was collected from two river mouths, both connected to caves. It belongs to the thermophilus group in showing 3,4,4,3 spine formula on legs 1-4 and lateral process on the genital double-somite. Among the members of the species group, it is closely allied with H. thermophilus Kiefer, 1929 and H. uncus Ueda and Nagai, 2009. However, it differs from them by a stout, lanceolate inner apical spine on leg 5 exopod, very short lateral process of the genital double-somite, short caudal rami, and shorter inner apical spine on the third endopodal segment of leg 4. Halicyclops pumilus was collected from interstitial waters of estuarine sandy beaches, and it is characteristic in having a single inner seta on the second endopodal segments of legs 2-3, and quadrate shape of leg 5 exopod with stumpy spines.